2019
DOI: 10.1111/trf.15352
|View full text |Cite
|
Sign up to set email alerts
|

How do I perform cell salvage in obstetrics?

Abstract: Maternal mortality in the United States is increasing. The leading cause of death is hemorrhage. Maternal hemorrhage can be profound, with entire blood volumes being lost. In most major blood loss surgery, autotranfusion (also known as cell salvage, cell saving, and intraoperative blood collection and readministration) is a technique that has been used to minimize allogeneic transfusion. Historically, autotransfusion has been considered contraindicated in the face of maternal hemorrhage because of a fear of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…[ 17–19 ] In summary, the primary and indispensable cryopreservation science for various biological samples (e.g., cells, tissues, organs, and vaccines) is vital for clinical applications and scientific research in the field of biomedical engineering. [ 20–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 17–19 ] In summary, the primary and indispensable cryopreservation science for various biological samples (e.g., cells, tissues, organs, and vaccines) is vital for clinical applications and scientific research in the field of biomedical engineering. [ 20–24 ]…”
Section: Introductionmentioning
confidence: 99%
“…Existing protocols for the collection and processing of blood in obstetrics are well documented and directed toward intraoperative blood collection during cesarean section. 2,10 Current protocols, however, do not address the specific challenges of vaginal blood collection, such as a mechanism to separate blood from amniotic fluid, or space and proximity barriers to access cell salvage equipment immediately in the delivery room. In our study, we observed that patients with severe hemorrhage following vaginal delivery are often moved to the operating room for management.…”
Section: Discussionmentioning
confidence: 99%
“…An area of particular interest includes cases with large QBL but a low volume of recovered blood and a low volume of autologous product transfused to the patient. Existing protocols for the collection and processing of blood in obstetrics are well documented and directed toward intraoperative blood collection during cesarean section 2,10 . Current protocols, however, do not address the specific challenges of vaginal blood collection, such as a mechanism to separate blood from amniotic fluid, or space and proximity barriers to access cell salvage equipment immediately in the delivery room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations